2018
DOI: 10.1007/s13318-018-0464-z
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Toxicology of the Neuroprotective e,e,e-Methanofullerene(60)-63-tris Malonic Acid [C3] in Mice and Primates

Abstract: The plasma half-life of C was 8.2 ± 0.2 h, and there was wide tissue distribution, including uptake into brain. The compound was cleared by both hepatic and renal excretion. C was quite stable, with minimal metabolism of the compound even after 7 days of treatment. The LD in mice was 80 mg/kg for a single intraperitoneal injection, and was > 30 mg/kg/day for sustained administration; therapeutic doses are 1-5 mg/kg/day. For primates, no evidence of renal, hepatic, electrolyte, or hematologic abnormalities were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…For example, there have been many reports of C 60 derivatives with less hydrophilic coverage than that of the present study, such as hydroxylated and carboxylated fullerenes, which showed greater retention in the lungs, muscle, and RES organs, in addition to longer residence times in vivo (~30 h) [26,38,41,[58][59][60][61]. However, leaving some lipophilic character on the C 60 surface can result in the penetration of certain restrictive membranes, such as the blood-brain-barrier, as was recently reported by Dugan and coworkers when administering 14 C-labeled e,e,e-methanofullerene(60)-63-tris malonic acid (C 3 ) [40]. C 3 showed significant liver and kidney uptake at 12 and 24 h p.i., which resulted in fecal excretion as the route of clearance.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…For example, there have been many reports of C 60 derivatives with less hydrophilic coverage than that of the present study, such as hydroxylated and carboxylated fullerenes, which showed greater retention in the lungs, muscle, and RES organs, in addition to longer residence times in vivo (~30 h) [26,38,41,[58][59][60][61]. However, leaving some lipophilic character on the C 60 surface can result in the penetration of certain restrictive membranes, such as the blood-brain-barrier, as was recently reported by Dugan and coworkers when administering 14 C-labeled e,e,e-methanofullerene(60)-63-tris malonic acid (C 3 ) [40]. C 3 showed significant liver and kidney uptake at 12 and 24 h p.i., which resulted in fecal excretion as the route of clearance.…”
Section: Discussionmentioning
confidence: 96%
“…Matrix-assisted laser desorption ionization mass spectrometry (MALDI-MS) was performed using an Autoflex MALDI An important aspect of designing drug delivery platforms is the study of the biodistribution and excretion profile of the compound. Thus far, the biodistribution profiles of C 60 reported in the literature, including C 60 -serinol, are discordant [38][39][40][41]. This work aims to reevaluate the in vivo behavior of this nanomaterial non-invasively, using the imaging technique positron emission tomography (PET).…”
Section: Synthesis and Characterization Of C60-cu(nota)mentioning
confidence: 99%
“…On the other hand, C 3 has several features which may prove attractive clinically. It acts catalytically (27), and therefore retains activity for as long as it is present, has a plasma half-life of 8 h, and demonstrates significant brain uptake in both rodents and non-human primates (29, 45). C 3 is also highly water soluble and has oral bioavailability (45).…”
Section: Discussionmentioning
confidence: 99%
“…It acts catalytically (27), and therefore retains activity for as long as it is present, has a plasma half-life of 8 h, and demonstrates significant brain uptake in both rodents and non-human primates (29, 45). C 3 is also highly water soluble and has oral bioavailability (45). While C 3 is roughly 100-fold less active than SOD itself (27), its ability to access mitochondria as well as other intracellular compartments may enhance its overall biological efficacy, especially as it appears to have a good safety profile with long-term (2 years, mice; 2 months, primates) chronic administration (19, 45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation